2014
DOI: 10.1016/j.foodcont.2014.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Catering services and HACCP: Temperature assessment and surface hygiene control before and after audits and a specific training session

Abstract: Proper application of HACCP in catering services involves monitoring decisive critical points. The purpose of this study was to assess food temperatures and surface hygiene control in two catering services in Navarra (Spain) at two different time periods: the first one after implementation of the HACCP system and the second period, after the initial supervision through audits and a specific training session regarding temperatures of products and hygienic conditions of surfaces and equipment because the majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 25 publications
3
44
1
6
Order By: Relevance
“…Start-up of the new legislation resulted in prevailing Class II for FCS (between 59.6% and 67.9%), Class III in hand swabs (over 90%) and Class I in cooling facilities (between 85.4% and 90.6%). Our results for FCS are in concurrence with research from Spain where the percentage of dirty surfaces was significantly reduced after implementing HACCP and training of staff (Garayoa et al, 2014). Although generic, these results show that such monitoring is important due to the fact that microbial contamination increases, over time, when using different food contact surfaces such as cutting boards (Schaffner, Sithole, & Montville, 2004).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Start-up of the new legislation resulted in prevailing Class II for FCS (between 59.6% and 67.9%), Class III in hand swabs (over 90%) and Class I in cooling facilities (between 85.4% and 90.6%). Our results for FCS are in concurrence with research from Spain where the percentage of dirty surfaces was significantly reduced after implementing HACCP and training of staff (Garayoa et al, 2014). Although generic, these results show that such monitoring is important due to the fact that microbial contamination increases, over time, when using different food contact surfaces such as cutting boards (Schaffner, Sithole, & Montville, 2004).…”
Section: Resultssupporting
confidence: 89%
“…Garayoa et al, set a limit at 0.6 log 10 CFU/cm 2 to distinguish clean (or satisfactory) and dirty (or unsatisfactory) surfaces (Garayoa et al, 2014), Dom enecheS anchez et al set the same limit at 1.3 log 10 CFU/cm 2 (Dom enech-S anchez, Laso, P erez, & Berrocal, 2011) while de Oliveira et al set their limits at 1.7 log 10 CFU/cm 2 (de Oliveira et al, 2014). Different authors emphasize different factors that influence the decision about the limit, such as season of the year, type of food contact surface material, legislation, etc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lucca and Torres (2006), Oliveira et al (2014) and Martins and Rocha (2014) revealed nonconformance in cleaning and disinfection of equipment and utensils practices. Garayoa et al (2014) observed that the degree of cleanliness of equipment and utensils was influenced by their place of storage. Utensils that were located below work areas were dirtier than those placed on high shelves or separated from working areas.…”
Section: Resultsmentioning
confidence: 99%
“…However, bacterial adhesion was significantly higher at the highest temperature tested (30 ºC). It has been reported that temperatures above 18 ºC and below 55 ºC can potentiate microbial development and food deterioration (Garayoa et al, 2014;Kim et al, 2013;Kuo and Chen, 2010). Additionally, 30 ºC may also be a critical temperature as it is the optimal growth temperature for many mesophilic bacteria, including pathogenic E. coli, Salmonella spp., and Bacillus cereus (Kim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%